2021
DOI: 10.3390/ijerph18115721
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Sports-Based Physical Activity Dropouts in University Students

Abstract: Despite extensive evidence reporting the numerous health benefits of physical activity, recent studies show that many people (60%) do not follow the recommendations to meet the accepted minimums of physical activity. Some of the main problems in today’s society are the high dropout rates (35%) and low adherence to the conditions for achieving the physical activity recommendations. The aim of the study is to analyze the reasons for dropout from sports that the participants particularly liked, to design a new sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 65 publications
0
9
0
1
Order By: Relevance
“…It was noteworthy that university students with more discretionary time had the worst PA. Surveys indicated that their lack of PA may be due to lack of time (commitment to other activities not related to physical activity) and fatigue [ 76 ]. High parental literacy was negatively associated with PA of adolescents, and the explanation may be similar to its effect on diet.…”
Section: Discussionmentioning
confidence: 99%
“…It was noteworthy that university students with more discretionary time had the worst PA. Surveys indicated that their lack of PA may be due to lack of time (commitment to other activities not related to physical activity) and fatigue [ 76 ]. High parental literacy was negatively associated with PA of adolescents, and the explanation may be similar to its effect on diet.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical evidence suggests that life transitions can have a negative impact on sport participation, particularly the transition to adulthood [ 9 , 10 , 11 , 12 ]. During this transition—marked by major life events such as going from primary to secondary school, starting a study, getting married, and becoming a parent—the likelihood of stopping practising sport increases, posing a threat to sustainable sport participation during the life course [ 11 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regular PA is associated with a reduced risk of all-cause mortality, cardiovascular disease, type 2 diabetes, many cancers, as well as better mental health and quality of life [ 9 , 10 , 11 ]. Public health guidelines recommend that university students have at least 150 min of moderate physical activity (MPA) or 75 min of vigorous physical activity (VPA) per week [ 12 , 13 , 14 ]. Sedentary behavior (SB) is a conscious activity characterized by low energy expenditure and performed in a sitting or reclining position, such as watching TV, reading, or driving [ 15 ].…”
Section: Introductionmentioning
confidence: 99%